The 500 hats of Bartholomew Cubbins - Seuss, Dr. (London, Collins, 1966)
Each time Bartholomew Cubbins attempts to obey the King's order to take off his hat, he finds there is another one on his head.
Keywords: Hats -- Fiction; Fairy tales